2014
DOI: 10.1158/2159-8290.cd-13-0286
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of the Residual Disease of Triple-Negative Breast Cancers after Neoadjuvant Chemotherapy Identifies Actionable Therapeutic Targets

Abstract: Neoadjuvant chemotherapy (NAC) induces a pathologic complete response (pCR) in approximately 30% of patients with triple-negative breast cancers (TNBC). In patients lacking a pCR, NAC selects a subpopulation of chemotherapy-resistant tumor cells. To understand the molecular underpinnings driving treatment-resistant TNBCs, we performed comprehensive molecular analyses on the residual disease (RD) of 74 clinically-defined TNBCs after NAC including next-generation sequencing (NGS) on 20 matched pre-treatment biop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
409
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 425 publications
(442 citation statements)
references
References 48 publications
(64 reference statements)
23
409
3
1
Order By: Relevance
“…In triple-negative breast cancer, the establishment and molecular profiling of PDXs from residual cancer cells that persist after neoadjuvant treatment (minimal residual disease (MRD)) may lead to the identification of targetable molecular alterations in the chemotherapy-resistant component of the tumour, which may mirror micro-metastases that are destined to clinically recur 68 .…”
Section: Pdx Models Of Treatment-resistant Diseasementioning
confidence: 99%
“…In triple-negative breast cancer, the establishment and molecular profiling of PDXs from residual cancer cells that persist after neoadjuvant treatment (minimal residual disease (MRD)) may lead to the identification of targetable molecular alterations in the chemotherapy-resistant component of the tumour, which may mirror micro-metastases that are destined to clinically recur 68 .…”
Section: Pdx Models Of Treatment-resistant Diseasementioning
confidence: 99%
“…The PIK3CA mutation frequency in MPBC thus appears to be greater than the 25% frequency listed for all types of breast cancer 50 and for TNBCs as a group. 51 PIK3CA mutations have been linked to improved outcomes in breast cancer. 52 The PI3K pathway is now widely considered a target of therapy for cancer in general 53 and for breast cancer, in particular.…”
Section: Resultsmentioning
confidence: 99%
“…TNBC subtype was more likely to develop bone metastases among Spanish patients (25.4 vs 18.5%) [80]. Balko et al evaluated 111 Peruvian TNBC who received chemotherapy and did not achieve pathologic complete response (pCR), and found that 57% belonged to basal-like, 18% to HER2-enriched, 5% to luminal A, 5% to luminal B and 4% to normal-like [81].…”
Section: Differences In Tumor Clinicopathological Featuresmentioning
confidence: 99%